2018
DOI: 10.1111/1759-7714.12628
|View full text |Cite
|
Sign up to set email alerts
|

IL‐37 inhibits invasion and metastasis in non‐small cell lung cancer by suppressing the IL‐6/STAT3 signaling pathway

Abstract: BackgroundIL‐37 has been identified as a fundamental inhibitor of inflammatory and immunity responses. It plays a crucial protective role in several cancers, but its anti‐tumor activity and the potential regulatory mechanism of IL‐37 in non‐small cell lung cancer (NSCLC) is largely unclear.MethodsEnzyme‐linked immunosorbent assay was used to detect plasma IL‐37 expression in NSCLC patients and healthy controls. The NSCLC cell line A549 was cultured with recombinant human IL‐37 or recombinant human IL‐6 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Similarly, Jiang et al found that serum IL‐37 level was decreased in NSCLC patients compared with healthy control. This low IL‐37 expression level was significantly associated with advanced TNM stage …”
Section: Il‐37 In Tumormentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Jiang et al found that serum IL‐37 level was decreased in NSCLC patients compared with healthy control. This low IL‐37 expression level was significantly associated with advanced TNM stage …”
Section: Il‐37 In Tumormentioning
confidence: 93%
“…53 level was significantly associated with advanced TNM stage. 54 A significant decrease in tumor growth was observed with IL-37 overexpression in a murine NSCLC model. 52 Tumor angiogenesis plays a crucial role for carcinogenesis and metastasis in NSCLC.…”
Section: Lung Cancermentioning
confidence: 95%
“…However, only limited studies have used cancer patient samples to investigate IL-37. 16,19,20 Furthermore, given its expression and role in immune cells, the expression of IL-37 in immune cells and its regulatory effects need to be investigated in cancer patients.…”
Section: Publicationmentioning
confidence: 99%
“…Indeed, the protective role of IL‐37 in cancer has been reported when IL‐37 was transfected into cancer cells, or when recombinant IL‐37 was administered in animal models of cancers (summarized in review papers by Ding et al and Abulkhir et al). However, only limited studies have used cancer patient samples to investigate IL‐37 . Furthermore, given its expression and role in immune cells, the expression of IL‐37 in immune cells and its regulatory effects need to be investigated in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, IL-37 has been demonstrated to inhibit the proliferation and invasion of cervical cancer cells through STAT3, and promoted cell apoptosis through Bcl-2-like protein 11 (15,16). In non-small cell lung cancer and renal cell carcinoma, IL-37 played an anticancer role through STAT3 (17). In gallbladder carcinoma, IL-37 acted as a tumor suppressor by inhibiting cell migration and invasion (18).…”
Section: Introductionmentioning
confidence: 99%